Elamipretide enhances post-thaw rooster sperm quality by mitigating oxidative stress and optimizing mitochondrial function during cryopreservation - Abouzar Najafi; Seyed Davood Sharifi; Ramin Farhadi; Shorsh Hussein Bapir (Scientific Reports)
Abstract Cryopreservation of rooster sperm is a vital technique in avian reproductive management; however, it is often hindered by oxidative stress induced by reactive oxygen species (ROS) that negatively impact sperm quality during the freezing-thawing process. The present study aimed to investigate the impact of elamipretide, a mitochondria-targeted peptide, on sperm quality post-thaw. Sperm samples from 32-week-old broiler breeder roosters were cryopreserved using a Lake extender buffer with glycerol as the cryoprotectant. Four different concentrations of elamipretide (0, 6, 9, and 12 µmol/L) were tested in combination with the extender. Post-thaw sperm quality was evaluated by assessing motility, kinematic parameters, membrane integrity, mitochondrial activity, ROS levels as a direct marker of oxidative stress, lipid peroxidation, cell viability, and antioxidant enzyme activities (SOD, GPx and TAC). Sperm motility increased significantly at the 6 µmol/L (60.33 ± 1.54) and 9 µmol/L (64.96 ± 1.96) concentrations compared to the control, with the highest straight-line velocity observed at 9 µmol/L (21.21 ± 0.59). Membrane integrity also improved significantly at 9 µmol/L (61.78 ± 2.70) compared to lower doses (36.30 ± 1.64) and decreased at 12 µmol/L (49.57 ± 1.63). ROS production was significantly lower at 6 µmol/L (2.88 ± 0.07). Mitochondrial activity peaked at 9 µmol/L (60.21 ± 1.92), reflecting enhanced cell vitality and function. However, the effects were diminished at 12 µmol/L, indicating toxicity at higher concentrations. This study demonstrates the potential of elamipretide to improve rooster sperm cryopreservation outcomes by mitigating oxidative damage and preserving sperm quality post-thaw.